Developing Country-Specific Question Prompt Lists About Dementia Palliative Care for Family Caregivers. (16th December 2020) - Bavelaar, Laura; van der Steen, Jenny; Nicula, Maria; Morris, Sophie; Kaasalainen, Sharon; Achterberg, Wilco; Brazil, Kevin
Abstract: We aimed to develop question prompt lists for family caregivers of nursing home residents with advanced dementia to augment advance care planning conversations. In the context of a joint European-Canadian study, we used standardized nominal group methods to create country-specific lists of questions. (Bereaved) family caregivers of persons with dementia read an information booklet about end-of-life care for people with dementia, and generated questions to ask healthcare professionals. They also marked the most important questions from pre-selected questions from other lists. In the Netherlands, 20 participants contributed to a question prompt list of 24 questions that gravitated towards questions about terminating life and the responsibilities of physicians and family involved in decision making. In Canada, 4 participants came up with a question prompt list of 15 questions, related mostly to staff-family communication, with some the same as selected in the Netherlands. Data from the other countries will be presented too.